An in vitro study to elucidate the effects of Product Nkabinde on immune response in peripheral blood mononuclear cells of healthy donors - Boitumelo Setlhare; Marothi Letsoalo; Siphathimandla Authority Nkabinde; Magugu Nkabinde; Gugulethu Mzobe; Gugulethu Mzobe; Andile Mtshali; Andile Mtshali; Sobia Parveen; Sobia Parveen; Samukelisiwe Ngcobo; Samukelisiwe Ngcobo; et al. (Frontiers Media S.A., 2024)
Introduction: A significant number of the South African population still rely on traditional medicines (TM) for their primary healthcare. However, little to no scientific data is available on the effects of most TM products on cytokine and cellular biomarkers of the immune response. We evaluated the impact of a TM [Product Nkabinde (PN)] in inducing cellular and cytokine biomarkers of immune response in peripheral blood mononuclear cells (PBMCs).Methods: PN, a combination of four indigenous South African plants was used in this study. The IC50 was established using the cell viability assay over 24 h. Luminex and flow cytometry assays were used to measure cytokine and cellular levels in PBMCs stimulated with PN and/or PHA over 24, 48, and 72 h, respectively. UPLC-HRMS was used to analyze an ethanol: water extract of PN to better understand the possible active compounds.Results: The IC50 concentration of PN in treated PBMCs was established at 325.3 μg/mL. In the cellular activation assay, the percentages of CD38-HLA-DR + on total CD4+ T cells were significantly increased in PBMCs stimulated with PN compared to unstimulated controls after 24 h (p = 0.008). PN significantly induced the production of anti-inflammatory IL-10 (p = < 0.001); proinflammatory cytokines IL-1α and IL-1β (p = < 0.001), TNF-α (p < 0.0001); and chemokine MIP-1β (p = < 0.001) compared to the unstimulated control after 24 h. At 48 h incubation, the production of proinflammatory cytokines IL-1α (p = 0.003) was significantly induced following treatment with PN, and IL-10 was induced (p = 0.006). Based on the UPLC-HRMS analysis, four daphnane diterpenoids viz., yuanhuacine A (1), gniditrin (2), yuanhuajine (3) and yuanhuacine (4) were identified based on their accurate mass and fragmentation pattern.Conclusion: The results show that PN possesses in vitro immunomodulatory properties that may influence immune and inflammatory responses. This study contributes to scientific knowledge about the immune effects of TM. More studies using PN are needed to further understand key parameters mediating induction, expression, and regulation of the immune response in the context of pathogen-associated infections.